Nonverbal Communication in Javanese and Australian Culture - Agus Subiyanto (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Non-verbal communication (NVC) is very common in social interactions, and the use of NVC is specified by social conventions. There are some universal nonverbal signals used by people across cultures such as laughing and crying, but there also some nonverbal acts which are culturally specific. This paper aims to discuss NVC in Javanese and Australian cultures. The data used in this study were taken from Javanese people living in Central Java and Australian people in Canberra. The respondents were chosen randomly. The results show that Australians and Javanese have similarities and differences in their types of nonverbal communication as handshakes, waving, kissing, hand holding, hugging and hand clapping. The styles of communication of these expressive movements are directly linked to cultural or social values within the two separate cultures